SISTEM KENDALI DAN MONITORING AIR CONDITIONER PADA ELEKTRIK ROOM CONTAINER CRANE BERBASIS ANDROID DENGAN SISTEM INTERNET OF THINGS - Andy Suryowinoto; Ilman Andi Pramono; Chandra Widyanto; Hery Irawan (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
A container crane is a crane used for loading and unloading containers at the port, one of which can function to lift containers from and to cargo ships. This crane propulsion system uses a mechanical system that is controlled by an electrical device that is cooled by an air conditioner. Therefore, a room temperature monitoring system is needed and the recording of cooling running hours is still done manually by officers, so it is still less efficient and effective. For this reason, researchers conducted research to be able to monitor and control the cooling system on an electric room container crane using the Internet of Things. The purpose of this study is to make it easier for officers to monitor the temperature of the container crane room so that the cooling air conditioner can work efficiently. The method on this prototype device has manual mode and automatic mode. In manual mode, the AC cooler will turn on and off depending on the switches in the application. In automatic mode, the cooling air conditioner will turn on and off depending on the given set point temperature. This tool also records the total running hour of the cooling air conditioner, so that officers can monitor how long the cooling air conditioner has been operating. In the main part of the hardware required embedded ESP32 for data connection and a real-time clock for scheduling tool operations. Tests, several times, found an average delay of about 3 seconds displayed on the application. Where the speed of data transmission is very dependent on internet speed so if the data connection is interrupted, it results in delays in data transmission. Overall, the device can work well according to its function.